A hydrophobic ionic liquid compartmentalized sampling/labeling and its separation techniques in polydimethylsiloxane microchip capillary electrophoresis. Issue 2 (31st October 2016) - Quan, Hong Hua; Li, Ming; Huang, Yan; Hahn, Jong Hoon
Abstract : This paper demonstrates a novel compartmentalized sampling/labeling method and its separation techniques using a hydrophobic ionic liquid (IL)—1‐butyl‐3‐methylimidazolium bis(trifluoromethylsulfonyl)‐imidate (BmimNTf2 )—as the immiscible phase, which is capable of minimizing signal losses during microchip capillary electrophoresis (MCE). The MCE device consists of a silica tube connected to a straight polydimethylsiloxane (PDMS) separation channel. Poly(diallyldimethylammonium chloride) (PDDAC) was coated on the inner surface of channel to ease the introduction of IL plugs and enhance the IL wetting on the PDMS surface for sample releasing. Electroosmotic flow (EOF)‐based sample compartmentalization was carried out through a sequenced injection into sampling tubes with the following order: leading IL plug/sample segment/terminal IL plug. The movement of the sample segment was easily controlled by applying an electrical voltage across both ends of the chip without a sample volume change. This approach effectively prevented analyte diffusion before injection into MCE channels. When the sample segment was manipulated to the PDDAC‐modified PDMS channel, the sample plug then was released from isolation under EOF while IL plugs adsorbed onto channel surfaces owing to strong adhesion. A mixture of flavin adenine nucleotides (FAD) and flavin mononucleotides (FMN) was successfully separated on a 2.5 cm long separation channel, for which the theoretical numbers of plates were 15 000 and 17 000, respectively. The obtained peak intensity was increased 6.3‐fold over the corresponding value from conventional electrokinetic injection with the same sampling time. Furthermore, based on the compartmented sample segment serving as an interim reactor, an on‐chip fluorescence labeling is demonstrated.